Rape, inequality and the criminal justice response in England: The importance of age and gender - Walker, Sarah-Jane Lilley (Criminology & criminal justice, 2021)
This article draws upon quantitative and content analysis of 585 reports of rape recorded within two police force areas in England in 2010 and in 2014 tracking individual incidents to eventual outcome to examine the impact, if any, of intersecting inequalities on trajectories of rape cases reported to police. The data were collected as part of the wider Economic and Social Research Council funded Justice, Inequality and Gender-Based Violence research project which examined victim-survivor experiences and perspectives on justice. Building on existing distinctions between types of rape case based on the relationship between victim-survivor and accused, the results suggest age and gender are significant factors in how sexual violence, and the criminal justice system, is experienced. While younger women and girls were disproportionately affected by certain types of sexual violence case and more likely to come into contact with the criminal justice system compared to men and older women, they were not necessarily more likely to achieve a conviction. The findings also confirm that some of the most vulnerable victims-survivors of sexual violence, especially those with poor mental health, are still not achieving criminal justice. Victims-survivors from Black and minority ethnic group or lesbian, gay, bisexual, transgender, transsexual, queer groups are underrepresented within the criminal justice system, implying these groups are not seeking a criminal justice response in the same way as ‘white’ heterosexual victims-survivors.